Cancer Incidence and Mortality Rates in Multiple Sclerosis: A Matched Cohort Study. (26th January 2021) - Marrie, Ruth Ann; Maxwell, Colleen; Mahar, Alyson; Ekuma, Okechukwu; McClintock, Chad; Seitz, Dallas; Webber, Colleen; Groome, Patti A.
Abstract : Objective: To determine whether cancer risk differs in people with and without multiple sclerosis (MS), we compared incidence rates and cancer-specific mortality rates in MS and matched cohorts using population-based data sources. Methods: We conducted a retrospective matched cohort study using population-based administrative data from Manitoba and Ontario, Canada. We applied a validated case definition to identify MS cases, then selected 5 controls without MS matched on birth year, sex, and region. We linked these cohorts to cancer registries, and estimated incidence of breast, colorectal, and 13 other cancers. For breast and colorectal cancers, we constructed Cox models adjusting for age at the index date, area-level socioeconomic status, region, birth cohort year, and comorbidity. We pooled findings across provinces using meta-analysis. Results: We included 53, 983 MS cases and 269, 915 controls. Multivariable analyses showed no difference in breast cancer risk (pooled hazard ratio [HR] 0.92 [95% confidence interval (CI) 0.78–1.09]) or colorectal cancer risk (pooled HR 0.83 [95% CI 0.64–1.07]) between the cohorts. Mortality rates for breast and colorectal did not differ between cohorts. Bladder cancer incidence and mortality rates were higher among the MS cohort. Although the incidence of prostate, uterine, and CNS cancers differed between the MS and matched cohorts, mortality rates did not. Conclusion: The incidence of breast and colorectal cancers does not differ between persons with and without MS; however, the incidence of bladder cancer is increased. Reported differences in the incidence of some cancers in the MS population may reflect ascertainment differences rather than true differences.